Embedding the Notion of Child- and Family-Centered Care into Organizational Practice: Learning from Organizational Visioning. Issue 2 (15th March 2017) - van Veelen, J. S. M.; Regeer, B. J.; Broerse, J. E. W.; van de Poel, S. F. P.; Dinkgreve, M. A. H. M.
ABSTRACT: Child- and family-centered care has permeated the practices of child welfare as a means to address fragmentation. Case management appears promising, but the approach is still in its infancy. This article aims to provides an understanding of the emergent organizational vision of a new approach to case management at multiple organizational levels. The authors conducted a case study on the implementation of Intensive Family Case Management in a Dutch organization that provides child and youth protection services. The focus is on the continuous and bottom-up process of visioning, which has helped to define the shared organizational vision. The key finding was an emerging, widely shared vision that is congruent at many organizational levels and that contrasts starkly with the old work approach. The conclusion is that innovative child- and family-centered approaches to case management are inherent to a multi-level organizational system that is consistent with the approaches it advocates, being embedded in organizational structures and embodied in practitioners' mindsets.